PENERAPAN MODEL COOPERATIVE LEARNING TIPE STAD UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR SISWA - Sonjaya, Trisna; Aeni, Ani Nur; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
After making observations on the material of natural appearance found some problems related to the low assessment of student learning outcomes, caused by the learning process using conventional methods, so that the impact on the low social skills and student learning outcomes. Improvement actions in classroom learning thought class action research actions (PTK) with revisions of Lewin model According to Elliot thought the implementation of the STAD Cooperative Learning Model Type which performed three cycles of action. The result of the study’s action in that the increase of learning result in the initial data is 24% increase in cycle I to 32%, then increase to 68% in cycle II, and increase again to 88% in cycle III. The result of this study has reached the target that has been determined with the specified target 85%. Theyfore, the application of Cooperative Learning Model STAD Type can inprove the skills especially social and related things student learning outcomes on the material appearance of nature in class V SDN Cigentur Tanjungkerta Subdistrict Sumedang District.